2020
DOI: 10.1007/s40195-020-01045-9
|View full text |Cite
|
Sign up to set email alerts
|

Preternatural Hexagonal High-Entropy Alloys: A Review

Abstract: Recently, various topics on high-entropy alloys have been reported and great amounts of excellent properties have been investigated, including high strength, great corrosion resistance, great thermal stability, good fatigue and fracture properties, etc. Among all these research activities, high-entropy alloys tend to form face-centered-cubic (FCC) or body-centeredcubic (BCC) solid solutions due to their high-entropy stabilization effect, while the hexagonal structures are rarely reported. Up to now, the report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 72 publications
(78 reference statements)
0
21
0
Order By: Relevance
“…As a novel high-strength and toughness multi-component alloy material, its inherent high-entropy effect [17,18] can inhibit the formation of intermetallic second phases. Therefore, HEAs often form simple solid solutions instead of many complex phases and thus have many excellent properties and characteristics, such as high strength, high toughness, high corrosion resistance, high wear resistance [19,20]. At the same time, due to the particular structure of HEAs, it is easy to perfectly combine strength, ductility, thermal stability, and oxidation resistance, which greatly meets the maximally demanding requirements for materials.…”
Section: Development Of High-entropy Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…As a novel high-strength and toughness multi-component alloy material, its inherent high-entropy effect [17,18] can inhibit the formation of intermetallic second phases. Therefore, HEAs often form simple solid solutions instead of many complex phases and thus have many excellent properties and characteristics, such as high strength, high toughness, high corrosion resistance, high wear resistance [19,20]. At the same time, due to the particular structure of HEAs, it is easy to perfectly combine strength, ductility, thermal stability, and oxidation resistance, which greatly meets the maximally demanding requirements for materials.…”
Section: Development Of High-entropy Alloysmentioning
confidence: 99%
“…(3) Other strengthening phases precipitated on the BCC matrix, such as HCP [20,52] Al x Zr 5 [53,54], M 5 Si 3 [55][56][57], etc.…”
Section: Reported Microstructure Of Rheasmentioning
confidence: 99%
“…In this context, rareearth concentrated multi-principal-element systems or so-called high-entropy alloys (HEA) open up great perspectives in the search for efficient magnetic refrigerants. Recent studies of rare-earth HEAs have revealed complex magnetism and interesting caloric effects in these materials [11][12][13][14][15][16][17][18][19]. All these multicomponent alloys demonstrate strong magnetocaloric effect (MCE) over a wide temperature span (a table-like behavior) and consequently increased relative cooling power (RCP).…”
Section: Introductionmentioning
confidence: 99%
“…are known for their excellent resistant to heat, wear and to high temperature oxidation [10] and these properties make them good elements for HEAs. In literature, most of the studies of RHEAs have been based on face-centredcubic (FCC) or body-centred-cubic (BCC) [6], [7], [11]- [13] with a very few on hexagonal closed-packed (HCP) structures [5], [14]- [16]. Elastic properties provide fundamental insight into crystal structure and nature of bonding in materials, and help in predicting the mechanical behaviour of materials.…”
Section: Introductionmentioning
confidence: 99%